An unusual cause of cardiogenic shock after percutaneous coronary intervention – a case report - Krzych, Łukasz; Święch, Wojciech; Gołba, Krzysztof S.; Machej, Leszek; Morkisz, Łukasz; Bochenek, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Heart injury may be a life-threatening condition with heterogeneous aetiology. Iatrogenic injury is one of causes of heart damage which may result in hemodynamic deterioration, including cardiac tamponade. This paper describes a case report of a cardiac tamponade with cardiogenic shock and cardiac arrest following percutaneous coronary intervention in a 77-year-old patient.